Developing ELISA for antibodies to rinderpest virus (RPV) by using reference and partially purified RPV antigens - Özdarendeli, A; Bulut, H; Doymaz, MZ; Bolat, Y (Scientific Technical Research Council Turkey, 2003)
The aim of this study was to develop ELISA to examine antibodies against rinderpest virus (RPV) for vaccination programmes in the Malatya and Elazig regions. Serum samples from 180 clinically healthy cattle in Malatya were obtained in the spring of 1995 and 157 serum samples from cattle were taken in the spring of 1996 in Elazig. The 337 serum samples were investigated with ELISA. To design the ELISA, reference purified RPV antigen obtained from Pirbright Animal Health institute was used. RPV RBOK vaccine strain was provided by Central Veterinary Control and Research Institute, Ankara. It was used to infect the Vero cell line and was purified partially. The partially purified RPV antigen was used as a test antigen in ELISA. To compare the reference RPV antigen with the partially purified RPV antigen, 337 serum samples were subjected to ELISA. Antibodies to RPV were detected in 286 out of 337 (84.86%) cattle sera when the reference RPV antigen was used. However, when the same serum samples were examined in ELISA by using the partially purified RPV antigen, 223 out of 337 (66.17%) sera were positive. The sensitivity and specificity of partially purified RPV antigen were 75.87% and 88.24%, respectively. The developed ELISA with partially purified RPV antigen seems to be acceptable according to our results.
Kismi ve pürifiye si?ir vebasi virüs antijenleri kullanilarak ELISA'nin geliştirilmesi
Keywords: rinderpest virus; ELISA; antibody